Evaluation of Percutaneous tube Thoracostomy Performed by Trainee in both Trauma and non-Trauma Patients - Maula, Kulsum; Alam, Md Kamrul; Khalil, Md Ibrahim; Hasan, Md Nazmul; Faruq, Mohammad Omar (Bangladesh Critical Care Journal, 2021)
Background: Percutaneous Tube Thoracostomy (PTT) is an invasive procedure that can save life now and then in different traumatic and non-traumatic conditions. But still it is an enigma; how our trainee surgeons are at home in this procedure. Objectives: To evaluate the outcome of the percutaneous tube thoracostomy performed by trainee in both trauma and non-trauma patients. Study design: Prospective, Observational study. Duration of study was September, 2019 to February, 2019. Methods: All patients who need PTT in traumatic and non-traumatic conditions were selected by purposive sampling. Thereafter, they were scrutinized according to eligibility criteria and 96 patients were finalized. A pre-tested, observation based, peer-reviewed data collection sheet was prepared before study. Data regarding clinical and surgical outcome profile were recorded. Data were compiled, edited, analyzed. Results: Among 96 patients, the highest 32.29% belonged to age group 31-40 years and lowest 9.37% belonged to age group ≤20. The mean age of the respondents was 29.19±9.81. We found out of 96 patients, 70(72.91%) were indicated PTT for traumatic conditions and rest 26(27.08%) were indicated PTT for non-traumatic chest condition where 36(37.5%) had simple penumothorax, 21(21.87%) haemothorax, 14(14.58%) massive pleural effusion, 13(13.54%) tension pneumothorax, 10(10.41%) haemopneumothorax, and 2(2.08%) had pyothorax respectively. In 53.12% patients had right sided intercostal chest tube (ICT) insertion whereas 46.87% had left sided ICT insertion. In our study, 89.55 % tube was placed at normal anatomical position. Besides, 10.41% tube thoracostomy were performed deviated from anatomical site. Among 96 patients 62.5% patients had length of incision 2-3cm, 35.41% had >3cm and 2.08% had <2cm respectively. Out of 96 patients 75(78.13%) showed uneventful outcome whereas 21(21.87%) had complications including 11.15%(11) each had wound infection, 4.46%(4) subcutaneous emphysema, 4.28%(3) drain auto expulsion, 2.85%(2) hemorrhage, 1.45%(1) had non-functioning drain and empyema with ascending infection respectively (p=<0.05). Conclusion: PTT is a life saving procedure that is most frequently implemented in chest trauma patients of our country. In majority cases, outcome of PTT were uneventful (78.13). Besides this more than one third of patient had length of incision more than 3 cm that needed extra stitches and 10.41% cases PTT were placed other than the normal anatomical site. Trainees of Dhaka Medical College Hospital are doing well in their performance of PTT insertion but still some anatomical orientations are necessary to avoid operative and post-operative complications Bangladesh Crit Care J March 2021; 9(1): 28-33